Ekonomi Orang Tua Terhadap Hasil Belajar Siswa - Sudirman; Nurain Hasan; Fahrudin Zain Olilingo (Yayasan Pendidikan Sudirman Mandiri, 2025)
This study aims to determine the influence of parents’economic level on students’learning outcomes at SMP Negeri 1 Batudaa. The source of data is primary data. The data collection technique is through the distribution of questionnaires. The study populations are 74 students who are directly involved in arranging the report. The samples are 74 students or the entire population, so this research is population research. The data are analyzed using simple linear regression. The results show that the regression value and the results of hypothesis testing positively influance parents’economic level on students’learning outcomes at SMP Negeri 1 Batudaa. The influence of the economic level on learning outcomes is 56,40% and the remaining 43,60% isfluenced by variables that are not studied.